The Implication of Inquiry Learning Approach Toward Students’ Achievement in Biology of X Grade Students of SMA Negeri 2 Surakarta - Astri Setiawati; Alvi Rosyidi; Bowo Sugiyarto (BIO-PEDAGOGI, 2013)
This  research aims  are  to  find out:  1) the  influence  of inquiry  approach toward  student’s  achievement  in cognitive  domain;  2) the  influence  of inquiry approach toward  student’s  achievement  in affective  domain;  3) the  influence  of inquiry  approach toward  student’s  achievement  in pshycomotor domain;  4) the best approach toward student’s achievement; and 5) the  most effective approach toward student’s achievement of studying biology on X grade of SMA Negeri 2 Surakarta. This research is a quasi experiment research with randomized control only design using  inquiry  approach  and conventional  approach  as  independent variables  and student’s  achievement  of study  biology  as  the  dependent  variable. Here, it is acquired three classes as the samples, there are the student’s of class X-1  as  the  control  class, student’s  of  class X-2 as  the  first  experimental  class, and student’s  of class  X-3 as  the  second experimental  class. The  population of  this research is  all of the  student’s  was  X grade  of SMA  Negeri  2 Surakarta. The sample  of  this  research was  established by  cluster random  sampling. The techniques for collecting data are by using test, questionnaire, and documentation. The data were analyzed by anova and then by scheffe test. The  conclusion of this  research are:  1)  There  is  an influence  of inquiry approach toward  student’s  achievement  in cognitive  domain;  2) There  is  no influence of inquiry approach toward student’s achievement in affective domain; 3) There  is  an  influence  of inquiry  approach toward  student’s  achievement  in pshycomotor domain; 4) Modified free inquiry is the best approach to influence the  student’s  achievement  based on  cognitive  domain, guided inquiry  approach and modified free approach are better to influence the student’s achievement  on pshycomotor domain;  and 5) The  most  effective  approach to influence  the student’s achievement is modified free inquiry. Key Words: inquiry learning approach, achievement, Biology.